Orthostatic Hypotension and Concurrent Autonomic Dysfunction: A Novel Complication of Lung Transplantation - Deepika Razia; Sofya Tokman; Sharjeel Israr; Hesham Mohamed; Hesham Abdelrazek; Bhuvin Buddhdev; Ashwini Arjuna; Kendra McAnally; Samad Hashimi; Michael A. Smith; Ross M. Bremner; Rajat Walia; et al. (Journal of Transplantation)
Background. Persistent orthostatic hypotension (OH) is a lesser-known complication of lung transplantation (LTx). In this retrospective case series, we describe the clinical manifestations, complications, and treatment of persistent OH in 13 LTx recipients. Methods. We identified LTx recipients who underwent transplantation between March 1, 2018, and March 31, 2020, with persistent symptomatic OH and retrospectively queried the records for clinical information. Results. Thirteen patients were included in the analysis, 9 (69%) had underlying pulmonary fibrosis, and 12 (92%) were male. The median age, height, and body mass index at LTx were 68 years, 70 inches, and 27 kg/m2, respectively. Six (46%) patients were deceased at the time of chart abstraction with a median (IQR) posttransplant survival of 12.6 months (6, 21); the 7 remaining living patients were a median of 19.6 months (18, 32) posttransplant. Signs and symptoms of OH developed a median of 60 (7, 75) days after transplant. Patients were treated with pharmacological agents and underwent extensive physical therapy. Most patients required inpatient rehabilitation (n = 10, 77%), and patients commonly developed comorbid conditions including weight loss, renal insufficiency with eGFR <50 (n = 13, 100%), gastroparesis (n = 7, 54%), and tachycardia-bradycardia syndrome (n = 2, 15%). Falls were common (n = 10, 77%). The incidence of OH in LTx recipients at our center during the study period was 5.6% (13/234). Conclusions. Persistent OH is a lesser-known complication of LTx that impacts posttransplant rehabilitation and may lead to comorbidities and shortened survival. In addition, most LTx recipients with OH at our center were tall, thin men with underlying pulmonary fibrosis, which may offer an opportunity to instate pretransplant OH screening of at-risk patients.